Language Confusion at Gala Sky Ardiansyah in Fuji an Youtube Channel: Psycholinguistic Study - Silvy Supriyah; Odien Rosidin; Sundawati Tisnasari (Jurnal Disastri (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2025)
This research is a combined study of linguistic and psychology, namely psycholinguistics. This study aims to describe the forms of speech confusion in Gala Sky Andriansyah, a 3- year-old child on the Fuji an YouTube channel who is in the process of language acquisition. A child who is in the process of language acquisition will definitely experience the term confusion in language. Where confusion is unclear when speaking. This study is descriptive qualitative. With data collection techniques using listening techniques and note-taking techniques. The listening technique is carried out by listening to videos on the Fuji an YouTube channel, and the note-taking technique is a continuation of the listening technique. The data in this study are in the form of variable data in the form of words or utterances obtained from a child named Gala Sky Andriansyah. After conducting the study, the researcher obtained research results in the form of speech confusion carried out by Gala Sky Andriansyah, namely lipsing, slurring, stuttering, and cluttering.